2014
DOI: 10.1186/1471-2148-14-105
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting bodies of the social amoeba Dictyostelium discoideum increase spore transport by Drosophila

Abstract: BackgroundMany microbial phenotypes are the product of cooperative interactions among cells, but their putative fitness benefits are often not well understood. In the cellular slime mold Dictyostelium discoideum, unicellular amoebae aggregate when starved and form multicellular fruiting bodies in which stress-resistant spores are held aloft by dead stalk cells. Fruiting bodies are thought to be adaptations for dispersing spores to new feeding sites, but this has not been directly tested. Here we experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 19 publications
2
76
0
Order By: Relevance
“…Forming fruiting bodies by social amoebae is considered to be an adaptation for spore dispersal (27). This hypothesis was directly supported by experimental studies in which fruiting bodies were shown to increase the rate at which spores are acquired by a model invertebrate Drosophila melanogaster (27).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Forming fruiting bodies by social amoebae is considered to be an adaptation for spore dispersal (27). This hypothesis was directly supported by experimental studies in which fruiting bodies were shown to increase the rate at which spores are acquired by a model invertebrate Drosophila melanogaster (27).…”
Section: Discussionmentioning
confidence: 94%
“…Forming fruiting bodies by social amoebae is considered to be an adaptation for spore dispersal (27). This hypothesis was directly supported by experimental studies in which fruiting bodies were shown to increase the rate at which spores are acquired by a model invertebrate Drosophila melanogaster (27). Although the primary vectors for D. discoideum spore dispersal are unknown (27), it will be an interesting future subject to identify such vectors in nature and then determine whether volatile terpenes have a role in attracting such vectors to facilitate spore dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite variable investment in stalk formation among strains, the overall height of the stalk is still fairly consistent across strains and between populations, which might suggest some stabilizing selection on its dimensions. If stalk height is crucial for dispersal, as suggested previously (Smith et al ., ), then strains that allocate fewer cells to the stalk might experience trade‐offs between the immediate benefits of producing more spores by reducing stalk allocation and the ability to disperse those spores to new locations. Although the phylogenetic conservation of the stalk across dictyostelids suggests that dispersal is probably an important fitness component in this organism, a caveat to this interpretation is that the stalk may serve a different function in other dictyostelid species, especially those that produce extensive, nonupright stalks of indeterminate size, for example, by helping the migratory slug to bridge gaps in the soil (Gilbert et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining cells ascend the stalk, forming a globular sorus at the top where they differentiate into sturdy spores (29). In the sorus, spores are positioned for dispersal into more favorable environments, presumably through contact and transport upon animals (30). Multiple wild isolates of the amoeba D. discoideum, but not all of them, have been found to be stably associated with several bacteria species (24).…”
Section: Significancementioning
confidence: 99%